Activity-dependent ectopic action potentials in regular-spiking neurons of the neocortex - Zhang, Yizhen Z.; Sapantzi, Stella; Lin, Alice; Doelfel, Savannah R.; Connors, Barry W.; Theyel, Brian B. (Frontiers in Cellular Neuroscience, 2023)
Action potentials usually travel orthodromically along a neuron's axon, from the axon initial segment (AIS) toward the presynaptic terminals. Under some circumstances action potentials also travel in the opposite direction, antidromically, after being initiated at a distal location. Given their initiation at an atypical site, we refer to these events as "ectopic action potentials." Ectopic action potentials (EAPs) were initially observed in pathological conditions including seizures and nerve injury. Several studies have described regular-spiking (RS) pyramidal neurons firing EAPs in seizure models. Under nonpathological conditions, EAPs were reported in a few populations of neurons, including recent work from our group showing that EAPs can be induced in parvalbumin-expressing interneurons in the neocortex. Nevertheless, to our knowledge there have been no prior reports of ectopic firing in the largest population of neurons in the neocortex, pyramidal neurons, under nonpathological conditions.We report here that a large proportion (72.7%) of neocortical RS cells from mice can fire EAPs after a specific stimulus in vitro, and that most RS cells (56.1%) are capable of firing EAPs across a broad range of stimulus conditions. To elicit EAPs, we triggered orthodromic action potentials with either long, progressively increasing current steps, or with trains of brief pulses at 30, 60, or 100 Hz delivered in 3 different ways, varying in stimulus and resting period duration. Of the 37 RS neurons in which we were able to elicit EAPs, it took an average of 863.87 orthodromic action potentials delivered over the course of an average of 81.375 seconds before the first EAP was seen. We observed that some cells responded to specific stimulus frequencies while others were less selective, suggesting frequency tuning in a subset of the cells. Our findings suggest that pyramidal cells can integrate information over long time-scales before briefly entering a mode of self-generated firing that originates in distal axons. The surprising ubiquity of EAP generation in RS cells raisesThis is a provisional file, not the final typeset article interesting questions about the potential roles of ectopic spiking in information processing, cortical oscillations, and seizure susceptibility.